Preferensi Santri Terhadap Atribut Produk Bank Syariah Indonesia (BSI) Di Pondok Pesantren Darul Ulum (PPDU) Jombang - Ririn Susilawati; Abid Datul Mukhoyaroh (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
The Darul 'Ulum Islamic Boarding School (PPDU) is one of the largest Islamic boarding schools in Jombang Regency. PPDU has approximately 11,000 students with a total of 40 dormitories and 16 educational units. Formal education units start from State Madrasah Ibtida'iyah, Junior High School (equivalent), High School (equivalent) to University. Apart from providing religious education facilities and general education facilities, PPDU also collaborates with banks to make it easier for students to carry out banking transactions such as paying tuition fees, taking monthly transfer money from parents, and saving. One of the banks that has collaborated with PPDU is Bank Syariah Indonesia (BSI). This type of research is qualitative. The results of the research show that one of BSI's superior products in PPDU is the Easy Wadi'ah Savings. The success of the Easy Wadi`ah Savings product was followed by an increase in the number of customers at BSI PPDU. Easy Wadia`ah Savings is the product of choice for sharia banking products for the PPDU pesantren community with a total of approximately 1,000 (one thousand) students from the santri community. There are 3 (three) largest dormitories that are customers, namely: Hurun Inn, ArRisalah, and Bani Umar. And the most numerous education units in PPDU are: SMP DU1, SMA DU1, and SMA DU2.